TEACHER PROFESSIONALITY OF AL-ISLAM AND KEMUHAMMADIYAHAN (AIK) IN IMPLEMENTING RELIGIOUS VALUES FOR STUDENTS AT MUHAMMADIYAH NITIKAN SD YOGYAKARTA DURING THE COVID-19 PANDEMIC - St. Erfi Yulvira; Indhira Asih Vivi Y; Rina Yuliana; Yusutria; Yuzarion; Charles; Nurhasnawati; Yuherman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Lack of students' ability to read and understand Islamic teachings well, practice religious values and daily life, feelings of insecurity, individualistic, and hedonistic attitudes during the covid-19 pandemic are still found. The study described in this article is aimed to determine the teacher professionality of Al-Islam and Kemuhammadiyahan (AIK) in instilling religious values for students and teacher professionality in instilling religious values for students at SD Muhammadiyah Nitikan Yogyakarta during the Covid-19 pandemic. The type of research was descriptive qualitative research. The data sources were primary data and secondary data. Data were obtained through interviews, observation, and documentation. The data analysis used was data reduction, data presentation, and conclusion drawing. The results showed that the teacher professionality of Al-Islam and Kemuhammadiyahan (AIK) instilled religious values, had an educational background, and Muhammadiyahan as an organizational cadre who understood the vision, mission, and goals of schools and organizations. In addition, they had pedagogical, professional, personality, and social competence. They also could integrate religious values into the material contained in the lesson plans, using exemplary and habituation methods, and establishing good cooperation with parents and the community in controlling students.